Perkembangan Ilmu Filsafat Dalam Beberapa Perspektif - Ariyanti, Widi; Saefurohman, Asep (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study explores the development of philosophy from various perspectives, including historical, thematic, geographical, and methodological views. The historical approach traces the evolution of thought from classical to modern philosophers, while the thematic perspective examines key topics such as ethics, epistemology, and axiology. The geographical perspective compares philosophical traditions in different regions, such as the West and the East, and the methodological perspective highlights changes in philosophical research approaches and methods. The method used is a literature review with critical analysis of primary and secondary sources. The results of the study indicate that each perspective offers unique insights into the development of philosophy, reflecting the dynamics and complexity of this discipline. This study emphasizes the importance of a multidimensional approach in understanding the development of philosophy and its contributions to science and technology. The integration of Western and Islamic approaches is also examined, showing the potential for developing science that is ethical and spiritual. This research underscores that philosophy is a continually evolving discipline, always adapting to new contexts and challenges.